Cultural Values and Parental Psychology: A Multilevel Analysis from the Joint Effort Toddler Temperament Consortium - Lecannelier-Acevedo, F (American Psychological Association, 2024)
The present study aims to gain a greater understanding of the manner in which culture may impact parenting and, thus, child development by examining the relationship between cultural values, socialization goals (SGs), and parental ethnotheories (PEs). Specifically, this study examined links between cultural value dimensions (i.e., individualism/collectivism, power distance, masculinity/femininity, uncertainty avoidance, indulgence/restraint, and long-term/short-term orientation; Hofstede et al., 2010) and autonomous as well as relational SGs and PEs. We examined data collected from mothers of toddlers (N = 865) between 17 and 40 months of age (M = 26.88 months, SD = 5.65 months; 52% boys) from 14 nations represented in the Joint Effort Toddler Temperament Consortium. We hypothesized that: (a) Cultural values consistent with independent cultural ideals would be positively associated with SGs and PEs representative of greater autonomy and independence, and (b) Cultural values consistent with interdependent ideals would be positively associated with SGs and PEs representative of greater interrelatedness. Multilevel modeling was used to regress parental psychology on Hofstede’s cultural values. Support for these hypotheses was somewhat mixed; higher ratings of culture-level indulgence were associated with higher autonomous PEs, as well as with higher relational and autonomous SGs. Furthermore, higher ratings of culture-level masculinity were associated with lower relational PEs and with lower autonomous SGs. The results suggest differences in the effects for cultural values associated with parenting versus cultural values associated with child outcomes and highlight considerations related to dichotomous cultural frameworks. The findings help explain both individual- and country-level variations in aspects of parental psychology. © 2024 American Psychological Association